Aortic Elongation and Stanford B Dissection: The Tübingen Aortic Pathoanatomy (TAIPAN) Project. (August 2017) - Lescan, M.; Veseli, K.; Oikonomou, A.; Walker, T.; Lausberg, H.; Blumenstock, G.; Bamberg, F.; Schlensak, C.; Krüger, T.
Abstract : Objective/Background: Aortic elongation has not yet been considered as a potential risk factor for Stanford type B dissection (TBD). The role of both aortic elongation and dilatation in patients with TBD was evaluated. Methods: The aortic morphology of a healthy control group ( n = 236) and patients with TBD ( n = 96) was retrospectively examined using three dimensional computed tomography imaging. Curved multiplanar reformats were used to examine aortic diameters at defined landmarks and aortic segment lengths. Results: Diameters at all landmarks were significantly larger in the TBD group. The greatest diameter difference (56%) was measured in dissected descending aortas ( p < .001). The segment with the most considerable difference between the study groups with regard to elongation was the non-dissected aortic arch of patients with TBD (36%; p < .001). Elongation in the aortic arch was accompanied by a diameter increase of 21% ( p < .001). In receiver–operating curve analysis, the area under the curve was .85 for the diameter and .86 for the length of the aortic arch. Conclusions: In addition to dilatation, aortic arch elongation is associated with the development of TBD. The diameter and length of the non-dissected aortic arch may be predictive for TBD and may possibly be used for risk assessment in the future. This study provides the basis for further prospective evaluation of these parameters.